Real-World Data on the Practice of Chemoradiation with Select Cohort Consolidation Chemotherapy in High-Risk Locally Advanced Rectal Cancers (SOLAR study) - Yallala, Mounika; Krishnatry, Rahul; Shah, Anjali; Bhargava, Prabhat Ghanshyam; Ramaswamy, Anant; Baheti, Akshay; Saklani, Avanish; Engineer, Reena; Ankathi, Suman K.; Kazi, Mufaddal; Desouza, Ashwin; Ostwal, Vikas (South Asian Journal of Cancer, 2025)
Chemoradiation with capecitabine radiotherapy (Cape–RT) has been the standard of care as neoadjuvant treatment in locally advanced rectal cancer (LARC) for more than a decade. However, total neoadjuvant therapy has recently emerged as an alternative with the potential to impact survival outcomes; baseline outcomes with Cape–RT in real-world practice in the Indian context are not well known.Treatment-naive patients with adenocarcinoma on histology and clinical-radiologically diagnosed LARC who received Cape–RT from June 2014 to December 2021 after multidisciplinary discussion were included. Patients received a long course of conventionally fractionated external beam RT (45–50 Gy in 25#) with concurrent oral capecitabine at a dose of 1650 mg/m2/day. Post approximately 6 to 8 weeks of completion of Cape–RT, patients were evaluated clinically and by magnetic resonance imaging pelvis for total mesorectal excision (TME) in the multidisciplinary team meetings. The primary endpoint of the study was event-free survival (EFS), and the secondary endpoint was overall survival (OS) and pathological complete response (PCR) rates. EFS and OS were calculated using the Kaplan–Meier method.A total of 1,189 patients with a median age of 49 years (range: 15–95) were identified and included. A significant proportion of patients had high-risk characteristics, such as T3/T4 disease (94%) and node positivity (90%), and they involved circumferential resection margin (CRM) (51%) at baseline. Signet ring and mucinous histology were seen in 13 and 11% of patients. Two hundred and seventy-six patients (23%) required further consolidation chemotherapy (commonly CAPOX [capecitabine-oxaliplatin] or modified FOLFIRINOX [5-fluorouracil-leucovorin-irinotecan-oxaliplatin]) post-Cape–RT prior to attempting surgery due to either persistent CRM positivity, clinical T4 disease, prostate abutment, sphincter involvement (248 patients, 21%), or extensive bulky disease with poor response (12 patients, 1%). Overall, 14 patients (6%) had an interruption in RT and 22 (8%) in chemotherapy. Post-Cape–RT, with or without chemotherapy, 945 patients (79%) underwent TME. Chemotherapy post-TME was administered in 808 patients (78%). With a median follow-up of 54 months (range: 51.2–57.2), the 3- and 5-year EFS for the entire cohort was 73.2% (95% confidence interval [CI]: 70.6–75.8) and 64.3% (95% CI: 61.1–67.5), respectively, while the estimated 3- and 5-year OS was 81.3% (95% CI: 78.9–83.7) and 73% (95% CI: 70–76), respectively. On multivariate analysis, the presence of higher T stage (p < 0.001) and signet ring histology (p = 0.004) predicted inferior OS.Real-world data in a less-resourced setting concurs with published prospective and Western real-world data. This provides confidence in implementing consolidation chemotherapy in total neoadjuvant settings in countries with fewer resources.
Keywords: LARC; NACTRT (Cape–RT); TNT; signet ring adenocarcinoma; mucinous adenocarcinoma